Comparative study of the performance and economic value of a small engine fueled with B20 and B20-LPG as an effort to reduce the operating cost of diesel engines in remote areas - Sinaga, Nazaruddin; Mel, Maizirwan; Purba, D.W.I.; Syaiful, S.; , Paridawati (IOP Publishing, 2019)
Indonesia is an archipelagic country that has remote locations. In such areas, the price of diesel fuel might be very costly. Hence, it is very burdensome for the community because this type of fuel is needed by diesel engines to drive generator sets, agricultural and production purposes. The utilization of dual-fuel diesel-gas engine is expected as a solution to this problem. This experimental study was carried out to compare the performance and economic value of operating a small diesel engine both with B20 biodiesel fuel and B20-LPG dual-fuel, with a variation of engine operating parameters, namely engine speed, LPG fraction and engine throttle opening. The performance parameters observed were torque, power, brake specific fuel consumption and brake thermal efficiency. Experiments were carried out in the laboratory at throttle openings of 50% and 100% with an LPG fraction of 10% to 70%. It was found that the best performance of the dual-fuel engine occurred at the throttle opening of 100% and an LPG fraction of 70%. In this condition, there was a 20% reduction in BSFC maximum, and a maximum power increase of 12%, compared to a single-fuel engine. The BTE increased by 9%, and the engine torque increased by nearly 5%. It is concluded that the performance of the dual-fuel engine generally increases compared to the single file mode. Another exciting conclusion is that the use of dual-fuel B20-LPG engines reduces operating costs by up to 40%.